1998
DOI: 10.1029/97jc03760
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the near‐surface eddy kinetic energy in the California Current based on altimetric, drifter, and moored current data

Abstract: Abstract.Low

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
106
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 26 publications
25
106
2
Order By: Relevance
“…Recent observations have shown that the offshore propagation of EKE is a robust feature of the annual cycle in this region, with the maximum occurring in summer and fall in association with the seasonal cycle of coastal upwelling. We have examined an important question raised by satellite altimeter data and surface drifter data which show the surface EKE decreasing, and the offshore propagation of EKE apparently stopping, beyond about 127øW [Kelly et al, 1998]. Here we attribute the decrease to a specific processrathe transformation of upper ocean baroclinic shear EKE to deeper barotropic EKE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations have shown that the offshore propagation of EKE is a robust feature of the annual cycle in this region, with the maximum occurring in summer and fall in association with the seasonal cycle of coastal upwelling. We have examined an important question raised by satellite altimeter data and surface drifter data which show the surface EKE decreasing, and the offshore propagation of EKE apparently stopping, beyond about 127øW [Kelly et al, 1998]. Here we attribute the decrease to a specific processrathe transformation of upper ocean baroclinic shear EKE to deeper barotropic EKE.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the more recent efforts, made possible by the availability of long-term surface drifter data and satellite sea level data, have been directed at describing the seasonal cycle of the CC and eddy fields [Kelly et al, 1998 No serious explanation has been offered for the limited westward extent of the EKE at the surface, although Kelly et al [1998] As a direct result of the seasonal cycle of wind-forced coastal upwelling in the simulation, a region of maximum EKE appears at the surface near the continental slope in late spring of each year (Plate 3a). The largest EKE value at the surface is about 0.06 m 2 s -2, which is similar to that computed from the TOPEX data by Kelly et al [1998] shown in Plate 1.…”
Section: Introductionmentioning
confidence: 99%
“…The westward intensification of EKE within ∼200 km of the shore, as well as significant year-to-year variability, complicate the interpretation of the coastal response as compared to the situation for EBUs (Fig. 12 in Marchesiello et al 2003;Kelly et al 1998).…”
Section: Eddy Kinetic Energymentioning
confidence: 99%
“…Eddy Kinetic Energy (EKE) in EBUs is consequently modulated by the seasonal cycle of upwelling winds (Kelly et al 1998). Once generated, surface-intensified EKE propagates offshore at roughly the speed of long-wavelength baroclinic Rossby waves (Kelly et al 1998;Marchesiello et al 2003). EKE is also redistributed vertically as part of the barotropization tendency of balanced turbulence, thereby energizing the subsurface ocean (Haney et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation